Gambaran Kadar Trigliserida dan Tekanan Darah pada Masyarakat Perumahan Universitas Andalas - Caesar Rayhand Arrafif Nasution; Eti Yerizel; Nita Afriani (Lembaga Pengembangan Kinerja Dosen, 2025)
Hypertension is a disease that often causes death and complications related to cardiovascular disease. The prevalence of hypertension in Indonesia is 34.11%. One of the factors that influence the incidence of hypertension is high levels of the triglycerides in the blood (hypertriglycerida). This study aims to determine the description between triglycerides levels and the incidence of hypertension in the community of Bandar Buat Village. This research was a descriptive study with 29 respondents taken using total sampling techniques from secondary data of community service in the village of Bandar Buat in 2019. Data were selected based on inclusion criteria and exclusion criteria, the data were processed in table to generate frequency and percentages distribution. The results showed that the majority of respondents aged 18-50 years (55.1%), were women (58.6%). The results showed that respondents' triglycerides levels were dominated by hypertriglycerida (58.6%) and blood pressure classification was dominated by normotension (55.2%). Based on age, most people with hypertriglycerida and hypertension are above 50 years old. Based on sex, hypertriglycerida and hypertension both are sufferers more frequent in men. The number of percentage were 66.7%; 75% respectively. The conclusion of this research is the triglycerides level of respondents is dominated by respondents with hypertriglycerida, the majority are aged>50 years, male sex. The incidence of hypertension is high, with majority sufferers aged>50 years, male sex.